Tajikistan's Winter Energy Crisis : Electricity Supply and Demand Alternatives - Fields, Daryl; Kochnakyan, Artur; Mukhamedova, Takhmina; Stuggins, Gary; Besant-Jones, John (Washington, DC: World Bank, 2013)
Tajikistan's electricity system is in a state of crisis. Approximately 70 percent of the Tajik people suffer from extensive shortages of electricity during the winter. These shortages, estimated at about 2,700 GWh, about a quarter of winter electricity demand, impose economic losses estimated at over United States (US) 200 million dollars per annum or 3 percent of Gross Domestic Product (GDP). The electricity shortages have not been addressed because investments have not been made in new electricity supply capacity and maintenance of existing assets has not improved. The financial incentive for electricity consumers to reduce their consumption is inadequate as electricity prices are among the lowest in the world. Without prompt action to remedy the causes of Tajikistan's electricity crisis and with growing demand, the shortages could increase to about 4,500 GWh by 2016 (over a third of winter electricity demand) or worse. The World Bank undertook this study to assist the Government of Tajikistan (GoT) in finding ways to overcome the current electricity shortages and establish a sound basis for meeting the growing electricity demand in Tajikistan. The study focuses on the investments and policy reforms needed between now and 2020 to strengthen the financial, technical and institutional capacity of the Tajik power sector and prepare the GoT for undertaking a major expansion of power supply capacity. The study excludes large hydropower plants with storage, given their complexity and global experience that such projects are subject to delays. The winter electricity shortages are caused by a combination of low hydropower output during winter when river flows are low and high demand driven by heating needs. The GoT should focus its immediate attention on three ways to eliminate the current winter power shortages: 1) ambitious energy efficiency plans to reduce uneconomic power usage; 2) new dual-fired thermal power supply to complement the existing hydropower supply during winter; and 3) increased energy imports to leverage surplus electricity supply in neighboring countries.